Match analysis in elite men`s senior and youth water polo, classifying actions for margins of victory and advantage - Lupo, C.; Li Volsi, D.; Perazzetti, A.; Tessitore, A.; Melchiorri, G.; Ungureanu, A. N. (International Journal of Sports Science & Coaching, 2025)
The present study aimed to compare technical and tactical factors of elite men's senior and youth water polo matches, and evaluate the same analyses in relation to margin of victory (MoV; according to the final match outcome) and advantage (MoA; according to the current match score). A notational analysis on teams was performed on 97 (50 from seniors, 47 from youth, level) European Championship matches, considering technical and tactical offensive indicators focused on goals scored and penalties during even, counterattack, power-play; and types of power-play outcomes. Results mainly reported that senior matches are characterised by a higher occurrence of power-play actions than youth ones, whereas the opposite picture emerged for the occurrence of penalties. In addition, major is the MoV and higher is the chance of scoring goals in counterattack actions for senior level. Moreover, for both levels, a larger MoV results in a greater likelihood of scoring goals and performing a reduced occurrence of negative outcomes (e.g., missed shots, lost ball possession, or offensive fouls) during power-play actions. Conversely, a higher MoA is associated with an increased percentage of goals scored by senior teams during counterattacks relative to total match goals, and a higher percentage of goals scored during power-play situations compared to total power-play outcomes. Consequently, this study offers valuable insights for coaches working with different team age levels and match phases, emphasising the distinct playing profiles for both senior and youth levels, as well as the classifications of actions based on MoV and MoA.